Exploring the Role of Rationality in Determining the Scope of Contractual Responsibility Based on Imam Khomeini and Martyr Sadr’s Opinion - Seyed Muhammad Hassan Mousavi Khorasani (آموزه‌‌های فقه مدني, 2020)
The role of the “rational course” in the inference of Shari'a law has been more or less considered by the jurists. The point of difference is how to determine its status, conditions and validity. At the same time, the greater validity of the precepts of the meaningful transactions of the world indicates the importance of rationality in jurisprudence. (At the same time, the more general verdicts of the verdicts confirm the importance of rationality in jurisprudence.) The exquisite views of some jurists in the study of the material and spiritual components of the Sirae are the basis for the significant works in contractual responsibility. Based on the findings of this essay written in a descriptive-analytical manner, it can be said that, in addition to relying on the evidence of coercive assertion to substantiate the principle of contractual liability, this type of disclaimer is indisputable, and does not imply explicit or implied (This type of responsibility is certain and it is not correct to subject it to explicit or implied). therefore, article 221 of the Civil Code is incorrect. In addition, relying on the organic and instrumental role of the rational process in understanding the rules of loss, ala al-yad and prohibition of detriment, the radius of responsibility encompasses non-profit damages. The of liability covers the non-profit losses incurred. On this basis, the amended Articles 221 of the Civil Code and Note 2 of Article 515 of the Code of Civil Procedure have been proposed. The overall approach of this article is to endorse the theory of unity of accountability and is in line with jurisprudence. At the same time, however, it differs from the well-known view of jurists, in that it argues that coercive damages include non-profit damages. (At the same time, it differs from the famous view of jurists in that it is argued that forcible indemnification involves non-profit damages.) Definite non-profit damages whether due to usurpation of property, human imprisonment, or breach of contract.